Temporal variation in expression oftoxicity in transgenic cottons against bollworm, Helicoverpa armigera (Lepidoptera:Noctuidae) - SRlNIVASAN, R; UTHAMASAMY, S (The Indian Journal of Agricultural Sciences, 2011)
Whole leaf bioassays were conducted during 2002-03 with neonates of Helicoverpa armigera to study the variation in expression oftoxicity with 3 transgenic lines, Mech 162 Bt and Mech 184 Bt at TNAU, Coimbatore. The bioassay of plants was done at fortnightly intervals in growing phase when plants had commenced squaring,and the third leaf from top on main shoot of the plant was used. Data on the toxicity showed a consistent decline in the efficacy of transgenic cotton plants, high efficacy in early flowering stage and a subsequent decline from 90 to 100 days, synchronizing with early boll formation stage. Decline in larval mortality ranged from 10 to 15% 90 days after sowing. The results of growth inhibition bioassay revealed than mean weight of survivors of H. armigera larvae on Bt leaves and bolls incorporated